Optimized Haar-cascade Algorithm for Face Recognition and Authentication - Kuldeep Vayadande (International Journal of Intelligent Systems and Applications in Engineering, 2024)
What amuses biometrics is that it can be incorporated into various situations. Particularly, it can be used to conduct identification, security, and Internet security. A newly emerged biometric technology is related to 3D imagery of faculty features while delivering additional flow of volume to empirical verification of human faces as well as identification. Conversely, it is very difficult to manipulate with large amount of 3D faces data that may come with some problems including the dimensionality reduction issues problem fighting with. This process serves to define face recognition as a viable means of personal identification nowadays, typically used during security, human–computer interaction systems, among others, and thus opting for more efficient algorithms for embedded systems is no longer negotiable. The smallest platforms are now utilizing the concept of embedded face recognition as the latest trendsetter. Lastly, neural networks are being potentially integrated into the system as they are considered to give the artificial systems both the speed and the accuracy. The canvas combines the concept of which includes LBP and MTCNN that brings all the edges to an end. Despite the fact that the PCA method before had brought about success in the dimensionality reduction sphere, a manifold theory has now become the trend in the process of handling facial expressions which have added complexity to the situation. The document explains the applications of the Haar cascade and face detection components, which includes before processing grayscale images up to after processing like integration with the facial recognition system. Furthermore, the course is video-academic and practical in that during the duration it deals with real time applications and issues and ethics principles which are mostly internalized to a student. The algorithms Library which is built on the abilities of face detection is the main tool of the developers and the researchers, on the one hand, that are used not only for face detection and employment of it but also for diversification of the technology, on the other hand. Progress is after all implemented in a double sense. thus, while the definition exposes the issues of ethics and imprecision, the main problem with computer vision cannot be forgotten either. Further, this result-based rescue approach also delivers the idea that the university is an getting prepared university as it aids its students to expand relevant skills and knowledge that actually follow on every campus, contemporary society.